Au-nano particles and their - Rudolf, Rebeka; Zorko, Lidija; Anžel, Ivan (Anali PAZU, 2022)
The development of synthesis technology for the production of Au nano-particles with defined size, shape and composition, is a challenge and an important research field in nano-technology. Namely, gold nano-particles are very attractive because of their potentialuse in electro-chemistry and medicine, and also for the production of different nano-devices.